The Decision to Purchase Converse Shoes in Tangerang City is based on the Role of Brand Image - Maria Mersha D. C. Medellu; Raffi Ilham Sani (Journal of Finance and Business Digital, 2022)
Success in attracting the attention of consumers to decide to buy the products offered is very important for the company. This study aims to find out how one of the supporting factors, namely brand image, can influence consumer purchasing decisions for Converse shoes. The object of this research is 100 respondents who are residents of the city of Tangerang with data collection methods through questionnaires. The background of this research is that there are many variables that can be considered to influence purchasing decisions, including brand image. Along with the times that are supported by the rapid flow of information through technology in the social and cultural environment of society that influences people's lifestyles including dress styles and fashion trends.